Living high-Training low for 21 days enhances exercise economy, hemodynamic function, and exercise performance of competitive runners - Park, H.-Y.; Park, W.; Lim, K. (Journal of Sports Science & Medicine, 2019)
Living high-training low (LHTL) is performed by competitive athletes expecting to improve their performance in competitions at sea level. However, the beneficial effects of LHTL remain controversial. We sought to investigate whether 21 days of LHTL performed at a 3,000 m simulated altitude (fraction of inspired oxygen [FIO2]=14.5%) and at sea level can improve hematological parameters, exercise economy and metabolism, hemodynamic function, and exercise performance compared with living low-training low (LLTL) among competitive athletes. All participants (age = 23.5 ± 2.1 years, maximal oxygen consumption [VO2max] = 55.6 ± 2.5 mL/kg·min, 3,000 m time trial performance=583.7 ± 22.9 seconds) were randomly assigned to undergo LHTL (n = 12) or LLTL (n = 12) and evaluated before and after the 21 days of intervention. During the 21-day intervention period, the weekly routine for all athletes included 6-day training and 1-day rest. The daily training programs consisted of >4 hours of various exercise programs (i.e., jogging, high-speed running, interval running, and 3,000 m or 5,000-m time trial). The LHTL group resided in a simulated environmental chamber (FIO2 = 14.5%) for >12 hours per day and the LLTL group at sea level under comfortable conditions. The hematological parameters showed no significant interaction. However, LHTL yielded more improved exercise economy, metabolic parameters (oxygen consumption=-152.7 vs 32.4 ml/kg·30min, Eta2 = 0.457, p = 0.000; tissue oxygenation index=6.18 vs .66%, Eta2 = 0.250, p = 0.013), and hemodynamic function (heart rate = -234.5 vs -49.7 beats/30 min, Eta2 = 0.172, p = 0.044; stroke volume = 136.4 vs -120.5 mL/30 min, Eta2 = 0.191, p = 0.033) during 30 minutes of submaximal cycle ergometer exercise corresponding to 80% maximal heart rate before training than did LLTL. Regarding exercise performance, LHTL also yielded more improved VO2max (5.40 vs 2.35 mLkg·min, Eta2 = 0.527, p = 0.000) and 3,000 m time trial performance (-34.0 vs -19.5 seconds, Eta2 = 0.527, p = 0.000) than did LLTL. These results indicate that compared with LLTL, LHTL can have favorable effects on exercise performance by improving exercise economy and hemodynamic function in competitive runners.